(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years the applications of video water markings are need to extract the watermark without using the original data because of the enormous storage of the cover data. In order to get the better performance an efficient multiple video watermarking techniques using artificial jellyfish with H.265 video encoding is developed. The proposed approach deals with watermark extraction process. In the extraction process, initially, the videos are subdivided into sub videos. Then, each video is converted into frames. Then, DWT is applied for each frame. To enhance the DWT performance, the co- coefficients are optimally selected using an artificial jellyfish algorithm. After-that, the watermark encryption/decryption method is carried out, and a different type of media (gray image, color image) is used as watermarks. After the watermarking, the image is compressed using H.265 video encoding algorithm. The performance of the proposed method is analyzed in terms of different metrics and the proposed work is implemented in MATLAB. The performance of the proposed method is validated by performances metrics and compared with the DWT based watermarking approach.